Massive Hypertriglyceridemia (6200 mg/dL) Presenting as Acute Pancreatitis: First Reported Case from Nepal - Laudari, Shankar; Aryal, Shisir; Yadav, Kamlesh (Journal of National Heart and Lung Society Nepal, 2024)
Hypertriglyceridemia-induced acute pancreatitis (HTG-AP) is an uncommon but severe form of pancreatitis, usually occurring when serum triglyceride (TG) levels exceed 1000 mg/dL. We report the first documented case from Nepal of massive hypertriglyceridemia (6200 mg/dL) presenting as acute pancreatitis in an alcoholic and previously undiagnosed diabetic male. Early diagnosis, aggressive triglyceride-lowering measures, and supportive care resulted in full recovery.